1, 3, 4‐Oxadiazole Bridges: A Strategy to Improve Energetics at the Molecular Level. Issue 10 (21st January 2021) - Ma, Jinchao; Chinnam, Ajay Kumar; Cheng, Guangbin; Yang, Hongwei; Zhang, Jiaheng; Shreeve, Jean'ne M.
Abstract: Many energetic materials synthesized to date have limited applications because of low thermal and/or mechanical stability. This limitation can be overcome by introducing structural modifications such as a bridging group. In this study, a series of 1, 3, 4‐oxadiazole‐bridged furazans was prepared. Their structures were confirmed by 1 H and 13 C NMR, infrared, elemental, and X‐ray crystallographic analyses. The thermal stability, friction sensitivity, impact sensitivity, detonation velocity, and detonation pressure were evaluated. The hydroxylammonium salt 8 has an excellent detonation performance ( D =9101 m s −1, P =37.9 GPa) and insensitive properties (IS=17.4 J, FS=330 N), which show its great potential as a high‐performance insensitive explosive. Using quantum computation and crystal structure analysis, the effect of the introduction of the 1, 3, 4‐oxadiazole moiety on molecular reactivity and the difference between the sensitivities and thermal stabilities of mono‐ and bis‐1, 3, 4‐oxadiazole bridges are considered. The synthetic method for introducing 1, 3, 4‐oxadiazole and the systematic study of 1, 3, 4‐oxadiazole‐bridged compounds provide a theoretical basis for future energetics design. Abstract : A series of 1, 3, 4‐oxadiazole‐bridged furazans was prepared. The thermal stability, friction sensitivity, impact sensitivity, detonation velocity, and detonation pressure were evaluated. The hydroxylammonium salt 8 shows great potential as a high‐performance insensitive explosive. The synthetic method for introducing 1, 3, 4‐oxadiazole and the systematic study of 1, 3, 4‐oxadiazole‐bridged compounds provide a theoretical basis for future energetics design.